Thermal Diffusivity of Silver Metallic Nanoparticles in Clay Matrix - R., Zamiri; Zakaria, Azmi; Ahmad, Mansor; K., Shameli; M., Darroudi; Mahdi, Mohd Adzir; M. A., Mahdi; Husin, Mohd Shahril (INOE Publishing House, 2010)
In this work, we have applied thermal lens (TL) technique to measure thermal diffusivity of clay suspensions containing metallic silver nanoparticles (Ag-NPs) prepared by chemical reduction method in different concentration. This study carried out with diode laser (wavelength 514 nm, power 80mW) as the excitation source and intensity stabilized He-Ne laser as a probe beam. The results show that thermal diffusivity of fluid increases when Ag-NPs concentrations increase.